EXAMINING A MODEL OF INFORMATION TECHNOLOGY ACCEPTANCE BY USERS OF ENTERPRISE RESOURCE PLANNING - Pontoh, Grace T. (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2011)
Enterprise resource planning (ERP) system is a complex system that involves various stakeholders as users of ERP system within an organization. This research is the development of Hwang’s research (2005) who applies the implementation and adoption of ERP system in informal controls, such as self-control and cultural control. Perceived enjoyment as self-control and uncertainty avoidance as cultural control are used in the implementation of ERP systems and connected to technology acceptance variables for investigating the relationship between these variables. Field data taken through surveys of ERP system users in Indonesia (n=188) are analyzed by Amos. The results support the hypothesis of this research which shows that perceived enjoyment as self-control and uncertainty avoidance as cultural-control are important determinants of ERP system acceptance.